Moldova Financial Sector Assessment Program : Detailed Assessments of Compliance with Standards and Codes - World Bank; International Monetary Fund (World Bank, Washington, DC, 2021)
This detailed assessment of observance with the basel core principles for effective banking supervision is the first external comprehensive assessment of the system of banking supervision in Moldova. The assessment was conducted by Walter Zunic, World Bank and Stefan Spamer, Deutsche Bundesbank, in May 2004. The national bank of Moldova cooperated fully with the assessment team and provided extensive clarification in the form of documents and oral explanation. Their assistance is gratefully acknowledged. The assessment of observance of each of the core principles adopts a qualitative approach and is based on the core principles methodology document (October 1999). The assessment method consisted of examining the degree of observance of each of a principle's essential criteria and, where the assessors judged necessary, of the additional criteria, too. In addition to the responses to the International Monetary Fund (IMF) questionnaire by the national bank of Moldova, detailed information available on the national bank of Moldova's internet website facilitated the drafting of this report.